Asymmetric vibration of polar orthotropic annular circular plates of quadratically varying thickness with same boundary conditions - N., Bhardwaj; A.P., Gupta; Choong, K.K. (IOS Press, 2008)
In the present paper, asymmetric vibration of polar orthotropic annular circular plates of quadratically varying thickness resting on Winkler elastic foundation is studied by using boundary characteristic orthonormal polynomials in Rayleigh-Ritz method. Convergence of the results is tested and comparison is made with results already available in the existing literature. Numerical results for the first ten frequencies for various values of parameters describing width of annular plate, thickness profile, material orthotropy and foundation constant for all three possible combinations of clamped, simply supported and free edge conditions are shown and discussed. It is found that (a) higher elastic property in circumferential direction leads to higher stiffness against lateral vibration; (b) Lateral vibration characteristics of F-F plates is more sensitive towards parametric changes in material orthotropy and foundation stiffness thanC-C and S-S plates; (c) Effect of quadratical thickness variation on fundamental frequency is more significant in cases of C-C and S-S plates than that of F-F plates. Thickness profile which is convex relative to plate center-line tends to result in higher stiffness of annular plates against lateral vibration than the one which is concave and (d) Fundamental mode of vibration of C-C and S-S plates is axisymmetrical while that of F-F plates is asymmetrical.